O património industrial do rio Nabão: Contributo para a salvaguarda da antiga Fábrica de Fiação de Tomar - Miguel José Antunes Francisco (2021)
The city of Tomar shows a very dispersed territorial occupation throughout its development, having, nowadays, a notorious recognition in the national and internacional history panorama, presenting a set of buildings and monuments as National Heritage and, in the case of the Convent of Christ, a UNESCO World Heritage Site. The city's historical recognition is notorious however, this dissertation intends to deepen another side of the city's history, less recognised at the local level, regarding to its industrial legacy along the Nabão River as a crucial element in the city's development, which finds itself at risk due to its neglect state. Along the route of the Nabão River, there are several industries that have been established on its banks taking advantage of the hydraulic force that the river provided. These industries, killed like many others by the "tertiarization" at a global level, identify themselves today in a complete state of neglect, leaving aside all their value as industrial structures and symbols of history and memory, which was a phase of the evolution of both civilization and the municipality of Tomar. Besides all the existing industrial units along the river, this dissertation focuses essentially on the Spinning Factory in Tomar, having been one of the largest textile industrial units in the country, not only for its dimensions but also for its longevity, having been founded at the end of the XVIII century and resisted for more than two centuries. Its privileged location in the city center, its strong historical and social value and its state of ruin are elements that contributed to its choice as a case study. It is intended to demonstrate the potential and the value of these industrial spaces as new dynamic centers in the municipality, by presenting new intervention solutions for Industrial Heritage. Thus, it pretends to contribute to an intervention and to safeguard the Tomar Spinning Factory and to motivate other interventions both in the Nabão valley and in other industrial areas.